Pasture Feeding in Late Pregnancy Does Not Improve the Performance of Twin-bearing Ewes and Their Lambs - R. A. Corner-Thomas; P. J. Back; P. R. Kenyon; R. E. Hickson; A. L. Ridler; K. J. Stafford; S. T. Morris (Asian-Australasian Journal of Animal Sciences, 2015)
The present study evaluated the effect of controlled ryegrass-white clover herbage availability from day 128 until day 142 of pregnancy in comparison to unrestricted availability, on the performance of twin-bearing ewes of varying body condition score (BCS; 2.0, 2.5, or 3.0) and their lambs. It was hypothesised that under conditions of controlled herbage availability, the performance of lambs born to ewes with a greater BCS would be greater than those born to ewes with a lower BCS. During the period that the nutritional regimens were imposed, the pre- and post-grazing herbage masses of the Control regimen (1,070±69 and 801±30 kg dry matter [DM]/ha) were lower than the ad libitum regimen (1,784±69 and 1,333±33 kg DM/ha; p<0.05). The average herbage masses during lactation were 1,410±31 kg DM/ha. Nutritional regimen had no effect on ewe live weight, BCS and back fat depth or on lamb live weight, indices of colostrum uptake, maximal heat production, total litter weight weaned or survival to weaning (p>0.05). The difference in ewe BCSs and back fats observed among body condition groups was maintained throughout pregnancy (p<0.05). At weaning, ewes from the BCS2.0 group had lower BCS and live weight (2.4±0.2, 74.3±2.6 kg) than both the BCS2.5 (2.6±0.2, 78.6±2.4 kg) and BCS3.0 ewes (2.7±0.2, 79.0±2.6 kg; p<0.05), which did not differ (p>0.05). Ewe BCS group had no effect on lamb live weight at birth or weaning or on maximal heat production (p>0.05). Serum gamma glutamyl transferase concentrations of lambs born to BCS3.0 ewes were higher within 36 hours of birth than lambs born to BCS2.0 ewes and BCS2.5 ewes (51.8±1.9 vs 46.5±1.9 and 45.6±1.9 IU/mL, respectively [p<0.05]). There was, however, no effect of ewe body condition on lamb plasma glucose concentration (p>0.05). Lamb survival was the only lamb parameter that showed an interaction between ewe nutritional regimen and ewe BCS whereby survival of lambs born to BCS2.5 and BCS3.0 ewes differed but only within the Control nutritional regimen ewes (p<0.05). These results indicate farmers can provide twin-bearing ewes with pre- and post-grazing ryegrass-white clover herbage covers of approximately 1,100 and 800 kg DM/ha in late pregnancy, provided that herbage covers are 1400 in lactation, without affecting lamb performance to weaning. The present results also indicate that under these grazing conditions, there is little difference in ewe performance within the BCS range of 2.0 to 3.0 and therefore they do not need to be managed separately.